(untitled) (Jurnal Manajemen Bisnis, 2024)
This literature review examines the effectiveness of remote and hybrid work policies in contemporary workforce management practices. The study aims to explore the impact of remote work arrangements on employee productivity, job satisfaction, and work-life balance, as well as to identify best practices for organizational leaders in managing remote and distributed teams. A systematic review of existing literature was conducted, drawing on peer-reviewed journals, conference proceedings, and academic books. The research highlights the benefits of remote work, including increased productivity and job satisfaction, attributed to reduced workplace distractions and enhanced flexibility. However, challenges such as social isolation and blurred work-life boundaries also emerge. Hybrid work models, combining remote and in-office work, are identified as a promising solution to address these challenges while maintaining opportunities for collaboration. Effective leadership, characterized by transformational leadership styles and proactive communication strategies, is crucial for facilitating successful remote and hybrid work arrangements. The findings underscore the need for ongoing research to explore emerging trends and best practices in remote and hybrid work policies, with a focus on the long-term effects on employee well-being and organizational performance.